2011
DOI: 10.1142/s0217979211102022
|View full text |Cite
|
Sign up to set email alerts
|

CONSTRUCTION OF SnO2/SiO2/Si HETEROJUNCTION AND ITS LINEUP USING I–V AND C–V MEASUREMENTS

Abstract: Near-ideal n- SnO 2/n- Si heterojunction band edge lineup has been investigated with aid of I–V and C–V measurements. The heterojunction was manufactured by rapid thermal oxidation of Sn metal films prepared by thermal evaporation technique on monocrystalline n-type silicon. The experimental data of the conduction band offset ΔEc and valence band offset ΔEc were compared with theoretical values. The band offset ΔEc = 0.55 eV and ΔEv = 1.8 eV obtained at 300 K. The energy band diagram of n- SnO 2/n- Si HJ was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…In case of LiNbO3, in the visible region no excitation can accrue, since the electrons are tightly restricted that the energy in the ultraviolet region is required. The obtained results are synchronized with experimental value in other work [24].…”
Section: Optical Propertiessupporting
confidence: 86%
See 1 more Smart Citation
“…In case of LiNbO3, in the visible region no excitation can accrue, since the electrons are tightly restricted that the energy in the ultraviolet region is required. The obtained results are synchronized with experimental value in other work [24].…”
Section: Optical Propertiessupporting
confidence: 86%
“…The optical properties were measured via transmittance (T) spectrum in the range of 300-1100 nm double-beam Ultr-Violet (UV-vis) spectrophotometer (Shimadzu UV-Vis 1800, Japan). The incident photon energy was calculated as a function of wavelength (λ) by using [24] …”
Section: Methodsmentioning
confidence: 99%
“…Few studies have reported on the effect of laser irradiation on the PL and structural properties of PS [22,23]. It was mentioned that PL of PS depends on irradiating laser energy density for using in optical recording and storage information on the surface of Si [24].…”
Section: Introductionmentioning
confidence: 99%
“…Bragg’s formula was used to compute the interplanar distance (d) for the all sets of LN nanophotonics 76 79 . where, n is a positive integer number, and d is the value provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%